EU integration and its implications for Asian economies: What we know and what not - Rolf J. Langhammer; Rainer Schweickert (Kiel Institute for the World Economy (IfW), 2006)
In this paper, we analyse effects of EU integration on Asian countries. Since the early 1990s, it is especially the trade creation effect of monetary integration (so-called Rose effect) which is heavily debated in the literature. Recent papers seem to indicate that the Rose effect seems to be significant especially for countries like the old EU members which are already highly integrated in terms of trade and factor mobility. The potential discrimination effect against trade with third countries tends to increase with new member states entering EMU and could also affect Asian economies' exports to Europe. At the same time, so-called overlap or similarity indices for trade patterns show an increasing similarity between EU, US, and Japanese exports to Asia on the one hand and Asian and European exports to industrialized countries on the other hand. These observations are consistent with recent policy responses, i.e., the focus of European contingent protection on Asian competitors, the desire of Asian countries to negotiate free trade agreements (FTA) with the US and Japan, and the EU's response by probably entering into FTA negotiations with Asian countries, including ASEAN.
Keywords: F13; F31; F15; O52; O53; 330; Monetary Integration; Protection; FTA; Overlap Index; Europe; Asia; Trade; Europäische Integration; Europäische Wirtschafts- und Währungsunion; Außenhandelseffekt; Internationale Wirtschaftsbeziehungen; Protektionismus; Freihandelszone; EU-Staaten; Asien